Perancangan UI/UX Aplikasi e-wallet “MyBank” - Priyo Dwi Cahyo; Febrianta Surya Nugraha; Lilik Sugiarto (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
Financial technology innovation in the form of a digital wallet has attracted the public's attention. The efficiency offered by this payment system has made people start to switch from conventional payments to digital payments. Besides that, there are many other factors that influence multi-generations to use digital wallets as an alternative for their daily payments. The use of digital wallets is currently widely applied for online transportation transactions, purchases in e-commerce, to food and beverage delivery services. The method used in this study is the literature study method with the aim of knowing developments in the use of digital wallets in society from various journals sourced from Scholar and several websites that have been analyzed and processed by researchers. become a MyBank application. From the application made, it can be concluded that it is able to facilitate digital wallet users, especially in Indonesia. Especially after there are many digital wallet applications, the number of digital wallet users is increasing because of that the MyBank application will make it easier for users to make more transactions digitally.